2022
DOI: 10.9734/jammr/2022/v34i2131544
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use among Students of a Health Training institution in the North-east Region of Ghana

Abstract: Background: Despite contraceptive awareness and availability to the general population, including higher education institutions, unplanned pregnancies continue to increase. Aim: The study assessed contraceptive usage among female health students in the North-East Region, Ghana. Methods: A descriptive cross-sectional studydesign was used to assess contraceptive use among 143 female health students. The data was collected using an online survey, analysed descriptively, Chi-square test and logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The current study further revealed that the majority of respondents got contraceptives from pharmacies, and condoms were the most commonly used method. This is consistent with a similar study conducted in the North-East region of Ghana [15]. This could be because condoms are easily accessible at the pharmacy and also because condoms are the most appropriate contraceptive method used among unmarried people given its dual capacity to prevent STIs and unplanned pregnancy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study further revealed that the majority of respondents got contraceptives from pharmacies, and condoms were the most commonly used method. This is consistent with a similar study conducted in the North-East region of Ghana [15]. This could be because condoms are easily accessible at the pharmacy and also because condoms are the most appropriate contraceptive method used among unmarried people given its dual capacity to prevent STIs and unplanned pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…The region became one of the two regions in Ghana with a high prevalence of teenage pregnancy in 2016 accounting for 15.5% of the national prevalence with the contraceptive acceptance among young people in the Kpando Municipality very low as compared to the adult population [17]. The HIV population among young adults 15-24 years increased between 2018 (34,219) to 2022 (40,497) and that of adolescents (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years) stood at 21,439 in 2022 [18,19]. The national prevalence of HIV reduced from 2.1% in 2018 to 1.8% in 2022 [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation